A DECISION-MAKING APPROACH TO THE FIRST TAX COURSE. - Raby, Wm. L. (The Accounting Review, 1964)
Abstract The typical tax course today utilizes a reference book as a text, focuses attention on the mechanics of the personal income tax, is taken almost exclusively by accounting majors, and accomplishes little that is educationally worthwhile except as the instructor injects background and philosophy from his own store of experiences. The author of the article like many others writers, has been experimenting with different ways of approaching the first tax course. His objectives agree with those of the American Accounting Association 1961 Committee on Income Tax Instruction. The problem of reaching agreement as to what are the underlying principles of income tax law is probably not much easier than that of defining accounting principles. Each general statement has a number of exceptions. Too often, there is a temptation to focus on the exceptions and ignore the rules. Author's broad objective in teaching is to communicate meaning. Author's basic orientation is directed towards business and investment decisions which also covers income, estate and gift taxes.